Syringocystadenocarcinoma Papilliferum In Situ–Like Changes in Extramammary Paget Disease: A Report of 11 Cases. (December 2016) - Konstantinova, Anastasia M.; Kacerovska, Denisa; Stewart, Colin J. R.; Szepe, Peter; Pitha, Jan; Sulc, Miroslav; Bencik, Vladimir; Michal, Michal; Shideler, Barbara; Kerl, Katrin; Kazakov, Dmitry V.
Abstract : Abstract: The authors report 11 cases of extramammary Paget disease (EMPD), all of which also demonstrated a combination of histological changes highly reminiscent of syringocystadenocarcinoma papilliferum in situ. In addition to the classical features of EMPD, characterized by the intraepidermal spread of individually dispersed neoplastic cells with ample cytoplasm, many of which contained mucin, there were areas of acanthosis with the substitution of spinous layer keratinocytes by neoplastic cells, whereas the native basal cell layer was intact. In addition to acanthosis (and sometimes papillomatosis), the dermal papillae showed a prominent infiltrate of plasma cells, completing the resemblance to syringocystadenocarcinoma papilliferum in situ; this similarity was further enhanced in 2 cases, which showed conspicuous gland formation. One additional case showed multifocal dermal proliferations compatible with eccrine syringofibroadenoma (syringofibroadenomatous hyperplasia). The changes described herein seem to be relatively rare in EMPD, and they can represent a diagnostic pitfall, as evidenced by 2 cases that were originally misinterpreted as syringocystadenocarcinoma papilliferum in situ. Clinically, these microscopic changes sometimes corresponded to nodular lesions, which were specifically noted to have a papillated erosive surface.